ANALYZING THE LEVEL OF CREDIT FAILURE USING THE AUTOREGRESSIVE DISTRIBUTED LAG TO MAINTAIN STABILITY OF COMMERCIAL BANKS IN MALUKU PROVINCE - Lewaherilla, Norisca; Sinay, Lexy Janzen; Damamain, Ferina Lestari; Sopaheluwakan, Marsa (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
Commercial banks are banks that carry out business activities conventionally and or based on sharia principles, which in their activities provide services in payment traffic. The health level of a commercial bank is the result of an assessment of the bank's condition based on risk and bank performance. Commercial Bank performance assessment can use the proxy of asset ownership, namely Return on Assets (ROA). While the risk assessment of commercial banks can use the credit risk proxy used is the Non-Performing Loan (NPL) ratio. The purpose of this study is to examine the Health Level of Commercial Banks in Maluku Province using ROA and NPL based on bank internal factors (bank specific) and macro and micro economic conditions in Maluku Province. The data used is quarterly time series data, namely in the first quarter of 2014 - first quarter of 2022. The method used is multivariate time series data analysis, namely the Autoregressive Distributed Lag (ARDL) model. The results obtained are the Health Level of Commercial Banks in Maluku Province in the first quarter of 2014 - first quarter of 2022 is classified as healthy and stable, even though the Maluku economy is experiencing the impact of the COVID-19 Pandemic. Internal (specific) bank factors are very dominant in influencing the performance and risk of Commercial Banks in Maluku Province compared to macro and micro economic factors. This means that the policies and performance of all parties related to Maluku's economic conditions need to be improved in maintaining the stability and soundness of commercial banks. In general, the performance of all parties in maintaining the health level of Commercial Banks in Maluku Province is very good, especially during the COVID-19 Pandemic.